(3QTMGJ GdCbdGe TQM caGjI GdZdGes - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd OGQ GdSdGe eHfjI Ydi CQcGf GdESdGe CeG HYO ajbhd GdYHO GdabjQ YHO GdZfi Hfi GdfGHdSi gPG TQM dWja GdYHGQI , hVYJg Ydi efXheJi GdeNJUQI GdLGeYI ddcdGe ai CQcGf GdESdGe s
(3BNQgG (B:s
(3bGd GdeUfa gPG BNQ eG CQOfG PcQg Ydi gPg GdefXheI ef GdTQM faY Gddg Hg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdESdGejs